HUBUNGAN KONFORMITAS SISWA DENGAN PENGAMBILAN KEPUTUSAN KARIR PADA SISWA SMA NEGERI 6 KOTA SEMARANG: HUBUNGAN KONFORMITAS SISWA DENGAN PENGAMBILAN KEPUTUSAN KARIR - Priambodo, Lukas (Jurnal Psikoedukasia, 2024)
The problem at SMA Negeri 6 Semarang is that students still have difficulty deciding on a career, such as choosing a study program to take at college. Students have not been able to find their own interests or motivation to determine a career after graduating from high school and are still heavily influenced by parents, teachers and the environment. The aim of this research is to determine and analyze the relationship between student conformity and career decision making. The research method uses ex post facto with a correlational research design. Data collection by observation, scale and documentation. The population is all class XII students, totaling 400 students with a sample of 100 students using proportional random sampling technique. Data analysis uses product moment correlation. The results of the research show that there is a significant relationship between student conformity and career decision making among students at SMA Negeri 6 Semarang City. The higher the student's conformity, the higher the career decision making.